2019
DOI: 10.1002/stem.3039
|View full text |Cite
|
Sign up to set email alerts
|

In Utero Transplantation of Expanded Autologous Amniotic Fluid Stem Cells Results in Long-Term Hematopoietic Engraftment

Abstract: In utero transplantation (IUT) of hematopoietic stem cells (HSCs) has been proposed as a strategy for the prenatal treatment of congenital hematological diseases. However, levels of long‐term hematopoietic engraftment achieved in experimental IUT to date are subtherapeutic, likely due to host fetal HSCs outcompeting their bone marrow (BM)‐derived donor equivalents for space in the hematopoietic compartment. In the present study, we demonstrate that amniotic fluid stem cells (AFSCs; c‐Kit+/Lin−) have hematopoie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Notably, human amniotic fluid stem cells (hAFS) have been highlighted as promising therapeutic strategyin regenerative medicine. hAFS have been shown to be broadly multipotent in vitro and in vivo [ 16 , 27 , 28 ], contribute to the hematopoietic lineage following in utero transplantation [ 29 ] and engraft in injured organs while exerting immunomodulatory effects [ 26 , 30 ] and activating endogenous reparative responses, as comprehensively described in [ 31 ]. Our team and others have further demonstrated that hAFS release a secretome highly enriched with bioactive trophic molecules able to target different reparative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, human amniotic fluid stem cells (hAFS) have been highlighted as promising therapeutic strategyin regenerative medicine. hAFS have been shown to be broadly multipotent in vitro and in vivo [ 16 , 27 , 28 ], contribute to the hematopoietic lineage following in utero transplantation [ 29 ] and engraft in injured organs while exerting immunomodulatory effects [ 26 , 30 ] and activating endogenous reparative responses, as comprehensively described in [ 31 ]. Our team and others have further demonstrated that hAFS release a secretome highly enriched with bioactive trophic molecules able to target different reparative mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Although the antigen surface expression is detected at the first passages (Di Trapani et al, 2013) and is gradually lost during expansion, cell selection makes hAFSC a peculiar population that maintains the ability to differentiate. Indeed, hAFSC can differentiate toward the hematopoietic (Ditadi et al, 2009;Loukogeorgakis et al, 2019), myogenic (Piccoli et al, 2012), and endothelial cells (Schiavo et al, 2015), not only in vitro but also in vivo and after secondary transplantation. In an elegant work, Xinaris and colleagues performed chimeric kidney organoids with hAFSC (after CD117 selection) and, strikingly, human cells contributed to the formation of glomerular structures, differentiating into podocytes (Xinaris et al, 2016).…”
Section: Human Amniotic Fluid Cells (Hafc)mentioning
confidence: 99%
“…Peranteau et al ( 2007) demonstrated that after transplantation of high doses of allogeneic or congenic BM cells into fetal mice, only 30% of allogeneic recipients sustained long-term chimerism, whereas 100% of congenic recipients remained chimeric. Recently, studies by Shangaris et al (2018) and Loukogeorgakis et al (2019b) showed that 100% of congenic recipients remained macrochimerism compared to 29% or 0% of allogeneic recipients with microchimerism after in utero transplantation of amniotic fluid stem cells. These results strongly suggest the engraftment advantage of congenic stem cells over allogeneic stem cells and the existence of immune barriers resulting in the elimination of allogeneic cells after IUHCT.…”
Section: Immunological Barriersmentioning
confidence: 99%